Prevalence of infection with Cryptosporidium parvumand Cyclospora cayetanensis among international travellers. Issue 6 (1st December 1997) - Jelinek, T; Lotze, M; Eichenlaub, S; Löscher, T; Nothdurft, H D
Abstract : Background — Cryptosporidium parvum and Cyclospora cayetanensis are recognised as possible pathogens of traveller's diarrhoea. Aims —To identify the prevalence of C parvum and Cyc cayetanensis in travellers returning from developing countries. Patients —Nine hundred and seventy eight stool samples were taken from 795 patients returning from developing countries. Methods —Microscopy (iron-haematoxylin stain, SAF concentration, modified acid fast stain) and a commercially available enzyme linked immunosorbent assay (ELISA) kit for the detection of Cryptosporidium antigen in stool. Results —Of the 795 patients in the study, 469 suffered from diarrhoea. Infection with Cyc cayetanensis could be detected in five subjects (1.1%) by acid fast stain, and 13 patients (2.8%) were infected with C parvum . On evaluation, the antigen capture ELISA turned out to be clearly less sensitive for detection of C parvum than microscopy. All patients with either C parvum or Cyc cayetanensis infection suffered from watery diarrhoea. Conclusions — C parvum and Cyc cayetanensis are not major causes of diarrhoea in international travellers. In cases of persistent watery diarrhoea, however, these pathogens should be taken into account in the differential diagnosis.